Public-Private Collaboration on Productive Development Policies in Costa Rica - Jorge Cornick; Jorge Jimenez; Marcela Román (Inter-American Development Bank (IDB), 2014)
Public-private collaboration in productive development policy in Costa Rica frequently takes the form of policy co-governance: an autonomous institution in charge of policy for a particular economic sector is created, with a board of directors comprising representatives from both the public and the private sectors, often with the public sector in a minority position. This paper analyzes five cases of co-governance: tourism, fisheries, rice, coffee, and the attraction of foreign direct investment (FDI). When co-governance has been used in conjunction with market discipline and as a means to discover and remove obstacles to higher productivity, as in tourism and FDI attraction, PDPs have been quite successful. When, on the contrary, it has been used to shield producers from market discipline or to allow unsustainable use of natural resources, as in rice and fisheries, they have turned into failures. Coffee stands in between, with considerable social achievements but only modest competitiveness achievements.
hdl:11319/6393
Keywords: F210; L520; O250; O430; 330; Foreign direct investment; FDI; Industrial policy; Sectoral planning; Economic growth; Institutions; Economic growth